Refugees and borders in South Asia : the great exodus of 1971 - Datta, Antara (New York : Routledge, 2012)
'The war in 1971 between India and Pakistan led to a huge refugee crisis. This book argues that the massive influx of ten million refugees into India within a few short months changed ideas about citizenship and belonging in South Asia.The book looks at how the Indian state, while generously keeping its borders open to the refugees, made it clear that these refugees were different from those generated by Partition, and would not be allowed to settle permanently. It discusses how the state was breaking its'effective' link between refugees and citizenship, and how at the same time a second'affective' border was developing between those living in the border areas, especially in Assam and West Bengal. The book argues that the present discourse regarding illegal infiltration from Bangladesh has a long historical trajectory in which the events of 1971 play a key role. It goes on to analyse the aftermath of the 1971 war and the massive repatriation project undertaken by the governments of India, Pakistan and Bangladesh to examine ways in which questions about minorities and belonging remained unresolved post-1971.The book is an interesting contribution to the history of refugees, border-making and 1971 in South Asia, as well as to studies in politics and international relations'--
'The war in 1971 between India and Pakistan led to a huge refugee crisis. This book argues that the massive influx of ten million refugees into India within a few short months changed ideas about citizenship and belonging in South Asia. The book looks at how the Indian state, while generously keeping its borders open to the refugees, made it clear that these refugees were different from those generated by Partition, and would not be allowed to settle permanently. It discusses how the state was breaking its'effective' link between refugees and citizenship, and how at the same time a second'affective' border was developing between those living in the border areas, especially in Assam and West Bengal. The book argues that the present discourse regarding illegal infiltration from Bangladesh has a long historical trajectory in which the events of 1971 play a key role. It goes on to analyse the aftermath of the 1971 war and the massive repatriation project undertaken by the governments of India, Pakistan and Bangladesh to examine ways in which questions about minorities and belonging remained unresolved post-1971. The book is an interesting contribution to the history of refugees, border-making and 1971 in South Asia, as well as to studies in politics and international relations'--
Includes bibliographical references (p. [185]-224) and index.
Includes bibliographical references and index.
Keywords: Political refugees -- India; Political refugees -- Pakistan; India-Pakistan Conflict, 1971.; HISTORY / Asia / India & South Asia; SOCIAL SCIENCE / Ethnic Studies / General